Transfer of Metals in Soil-Grass Ecosystems under Long-Term N, P, K Fertilization in Hesse, Germany. Issue 9 (15th May 2017) - Czarnecki, Sezin; Düring, Rolf-Alexander
ABSTRACT: Soil and plant samples (Lolio-Cynosuretum) were taken from four different locations in Hesse, Germany. Different doses of nitrogen, phosphorus, and potassium fertilizers were applied to verify metal input due to fertilization. Metal concentrations in plants increased due to mineral fertilization. Detected plant cadmium (Cd), copper (Cu), manganese (Mn), lead (Pb), and zinc (Zn) concentrations in non-fertilized plots were 0.04, 4.13, 106.5, 0.57, and 23.0 mg kg −1 and in long-term NPK-amended plots they were 0.31, 15.3, 524.9, 3.49, and 60.0 mg kg −1, respectively. Transfer factor (TF) was observed to decrease in the order of Cd>Cu>Zn>Mn>Pb. The results of regression analysis showed that organic carbon (Corg ) content, effective-cation exchange capacity (CECeff ), and bioavailable metal content are the most important predictors for plant metal uptake. This study confirmed that plant metal uptake was not only highly affected by the soil metal content but also influenced by soil properties.